2016
DOI: 10.1002/cmdc.201500552
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity, Selectivity, and Reaction Mechanisms of Aminoguanidine, Hydralazine, Pyridoxamine, and Carnosine as Sequestering Agents of Reactive Carbonyl Species: A Comparative Study

Abstract: Reactive carbonyl species (RCS) are endogenous or exogenous byproducts involved in the pathogenic mechanisms of different oxidative-based disorders. Detoxification of RCS by carbonyl quenchers is a promising therapeutic strategy. Among the most studied quenchers are aminoguanidine, hydralazine, pyridoxamine, and carnosine; their quenching activity towards four RCS (4-hydroxy-trans-2-nonenal, methylglyoxal, glyoxal, and malondialdehyde) was herein analyzed and compared. Their ability to prevent protein carbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 47 publications
4
66
0
Order By: Relevance
“…These findings are in line with recent studies demonstrating poor quenching activity of carnosine derivatives towards MG [14, 42]. Quenching capacity of carnosine is higher against other reactive metabolites such as acrolein and HNE [14, 40, 41, 43]. Although both, HNE and MG, belong to the group of reactive carbonyl species reacting with the nucleophilic groups in proteins, the two compounds are chemically distinct with both very different reaction kinetics leading to different stable end products.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are in line with recent studies demonstrating poor quenching activity of carnosine derivatives towards MG [14, 42]. Quenching capacity of carnosine is higher against other reactive metabolites such as acrolein and HNE [14, 40, 41, 43]. Although both, HNE and MG, belong to the group of reactive carbonyl species reacting with the nucleophilic groups in proteins, the two compounds are chemically distinct with both very different reaction kinetics leading to different stable end products.…”
Section: Discussionsupporting
confidence: 82%
“…Carnosine acts through two reactive moieties, one of the nitrogen atoms of the imidazole ring or the amino group nitrogen of the β-alanine residue. These nucleophilic nitrogens target the two reactive sites of α, β-unsaturated aldehydes, the aldehyde function or the electrophilic C3 atom [14]. Cellular uptake of carnosine occurs by proton-coupled oligopeptide transporters (POTs), membrane proteins that translocate various small peptides and peptide-like drugs across the biological membrane via an inwardly-directed proton gradient and negative membrane potential [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hydralazine contains a nucleophilic hydrazine moiety which binds with free and protein-bound aldehydes to form stable hydrazones [23,24 •• ]. In animal models of atherosclerosis, hydralazine administration was found to reduce athero- sclerotic lesion size and decrease carbonyl protein adducts within aortic sinuses, suggesting hydralazine possesses anti-atherogenic properties.…”
Section: Clinically Approved Agents With Aldehyde Scavenging Capacitiesmentioning
confidence: 99%
“…Comparison of carnosine scavenging of HNE, methylglyoxal, glyoxal, and MDA in vitro showed that carnosine was most effective at scavenging HNE [93]. In vivo evidence for the ability of carnosine to scavenge RCS include detection of HNE modified carnosine in the urine of Zucker fatty rats [94] and detection of acrolein-carnosine adducts in human urine [95].…”
Section: Reactive Carbonyl Species Scavengers Ameliorate Diseasementioning
confidence: 99%